An Empirical Analysis Of Investor Awareness And Perception Towards Capital Market Instruments. - V. Gopalakrishnan, V. Gopalakrishnan; A. Venkatesan, A. Venkatesan; Sathish, M. Thangajesu (Journal of Neonatal Surgery, 2025)
Capital market investment plays a vital role in promoting economic growth and enhancing individual wealth creation by providing opportunities for long-term financial returns. However, investment decisions are influenced by various demographic, psychological, and informational factors that shape investors' perceptions and behaviour. The present study aims to examine the perception towards the capital market, factors influencing investment decisions, and the challenges faced by investors. The study adopts a descriptive and analytical research design and is based on primary data collected from 180 respondents using a structured questionnaire through the Convenience Sampling technique. Secondary data were obtained from books, journals, research articles, government publications, and online sources. The collected data were analyzed using Percentage Analysis, Independent Samples t-test, and One-Way ANOVA to assess the relationship between demographic variables and investment-related perceptions and challenges. The findings indicate that respondents' investment decisions are primarily influenced by expected returns, risk perception, financial advice, availability of information, and ease of the investment process. The study also reveals that demographic variables such as age, monthly income, and area of residence significantly influence certain aspects of investment perception and challenges, whereas gender does not have a significant impact. The research emphasizes the importance of financial literacy, investor awareness, and simplified investment procedures in encouraging greater participation in the capital market. The findings provide useful insights for policymakers, financial institutions, investment advisors, and market regulators in formulating strategies to improve investor confidence and promote informed investment decisions...